INTERVENSI ABG SEBAGAI UPAYA MENCEGAH RISIKO DEMENSIA - Tarnoto, Koko Wahyu; Oktavia, Tessa (STIKES Permata Nusantara Cianjur, 2024)
The health problem that is often experienced by the elderly is dementia, which is often considered a common problem and is normal. Dementia (dementia) is a decrease in cognitive function such as easy forgetting, difficulty calculating and difficulty concentrating. Senile dementia can be prevented with non-pharmacological therapy, namely by implementing art therapy and board game interventions. The aim of this research is to determine the effectiveness of ABG intervention in preventing the risk of dementia. The method in this research is quantitative research with a pre-experimental design with a one group pretest-posttest design approach which is carried out before and after the intervention is given, measurements are taken using the HVLT instrument. The implementation time lasted 4 weeks and the population in this study was the elderly. The sampling technique in this research used purposive sampling in accordance with the inclusion and exclusion criteria. The number of samples in the study was 61 people. Inclusion criteria are elderly aged 60 years and over with a risk of dementia with HVLT score (< 14.5), elderly who live in the Jagalan sub-district area. The statistical test used is the Wilcoxon Signed Rank Test. The results of this study obtained a p-value of 0.000 < 0.05, which states that there is a significant influence of ABG intervention on efforts to prevent the risk of dementia in the elderly in the Pucang Sawit health center working area. In conclusion, it is hoped that ABG intervention will become a routine program in elderly posyandu activities in the work area at puskesmas.